Colovesical Fistula: An Uncommon Cause of Hematuria and Rectal Bleeding - Jeffrey K. Than; Greg S. Cohen (Case Reports in Gastrointestinal Medicine)
Colovesical fistula is an infrequent complication of diverticular disease that presents with pneumaturia, fecaluria, dysuria and, rarely, hematuria or hematochezia. Here we present a case of concurrent hematuria and rectal bleeding arising from a diverticular bleed traversing a previously undiagnosed colovesical fistula. Other causes of colovesical fistula include Crohn’s disease, radiation, and malignancy, though it is most commonly caused by complicated diverticulitis as in this case. Computed tomography (CT) imaging, cystoscopy, and gastrograffin enema have been described as high-yield diagnostic tests. Interestingly, colonoscopy is only successful in diagnosing colovesical fistula in approximately 55% of cases. Management often requires surgical intervention, as in this case, given limited success with conservative management. Colovesical fistula should be considered in patients presenting with fecaluria, pneumaturia, and dysuria as well as in cases of hematuria.